COOPERADOS E COOPERATIVA NAS REPRESENTAÇÕES E PRÁTICAS NA COASUL COOPERATIVA AGROINDUSTIAL - Fachin, Rosicléia (2009)
This work is the result of research developed over the Masters in Applied Social ciences by the University of Ponta Grossa, Paraná (UEPG), addressing the cooperative practices and representations of Coasul cooperative Cooperativa Agroindustrial, São João, PR. The Coasul was founded in 1969 and cooperated together over 3,000 of twenty counties in southwest and central region west of the state of Parana, with major economic, social and cultural life of thousands of people. Throughout its history developed economic activities related to agriculture, with the main crops of corn, soybeans and wheat, with production targeted for both domestic consumption for both large companies with marketing and industrialization. The objective of the research was studying how involved cooperated and how they perceive, interpret and give meaning to cooperative. Practices that are valued or not? How are they constructed the representations of these practices? These are the focuses of this fieldwork and theoretical, considering the history of the cooperative, the cooperative principles, the values defended by the cooperative practices and clashes with the reality of the experiences cooperated, their experiences. We tried to produce documentary records, obtained by participant observation such as stories of life and the field notebook. Were also used in the written tests, as Minutes of the Cooperative, which represent the life of the decisions cooperated, especially in time of foundation. It is expected, thus contributing to that reflects on the possibilities and limits of the traditional cooperative contemporary.